Patricia Harris papers - Harris, Patricia, 1924-1985.
Correspondence, memoranda, speeches, reports, statements, notes, printed material, and other papers pertaining primarily to Harris's cabinet positions as secretary, U.S. Dept. of Housing and Urban Development (HUD) (1977-1979) and secretary, Dept. of Health, Education, and Welfare (later, Health and Human Services) (1979-1981). Topics include abortion, civil rights, consumer protection, discrimination, energy, the environment, housing, inflation, immigration, Iran hostage crisis, nuclear energy, public welfare, social security, the Strategic Arms Limitation Talks II, and urban policy. Of special note are the meeting notes kept by Harris as a member of Jimmy Carter's cabinet. Also includes material relating to Harris's service as U.S. ambassador to Luxembourg (1965-1967) and to her candidacy for mayor of Washington, D.C., in 1982.
Correspondents include Geno C. Baroni, Robert C. Byrd, Jimmy Carter, Rosalynn Carter, Carolyn Sue Chin, Stephen F. Coyle, Stuart Eizenstat, Robert Campbell Embry, Jr., Henry A. Hubschman, Jay Janis, Vernon E. Jordan, Randolph S. Kinder, Albert J. Kliman, Ed Koch, William Antonio Medina, Walter F. Mondale, Pauli Murray, Tip O'Neill, William Proxmire, Donna E. Shalala, Nathan J. Stark, Cyrus R. Vance, William B. Welsh, Bill M. Wise, and Jim Wright.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer, educator, diplomat, and cabinet officer; born Patricia Roberts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baroni, Geno C. -- 1930-1984 -- Correspondence; Byrd, Robert C. -- Correspondence; Carter, Jimmy, -- 1924-; Carter, Jimmy, -- 1924- -- Correspondence; Carter, Rosalynn -- Correspondence; Chin, Carolyn Sue, -- 1947- -- Correspondence; Coyle, Stephen F. -- Correspondence; Eizenstat, Stuart -- Correspondence; Embry, Robert Campbell, -- 1937- -- Correspondence; Hubschman, Henry A., -- 1947- -- Correspondence; Janis, Jay, -- 1932- -- Correspondence; Jordan, Vernon E. -- 1935- -- Correspondence; Kinder, Randolph S. -- Correspondence; Kliman, Albert J. -- 1934- -- Correspondence; Koch, Ed, -- 1924-2013 -- Correspondence; Medina, William Antonio, -- 1935- -- Correspondence; Mondale, Walter F., -- 1928- -- Correspondence; Murray, Pauli, -- 1910-1985 -- Correspondence; O'Neill, Tip -- Correspondence; Proxmire, William -- Correspondence; Shalala, Donna E. -- Correspondence; Stark, Nathan J. -- Correspondence; Vance, Cyrus R. -- 1917-2002 -- Correspondence; Welsh, William B., -- 1924- -- Correspondence; Wise, Bill M., -- 1936- -- Correspondence; Wright, Jim, -- 1922- -- Correspondence; United States. -- Department of Health and Human Services. -- Office of the Secretary; United States. -- Department of Health, Education, and Welfare. -- Office of the Secretary; United States. -- Department of Housing and Urban Development. -- Office of the Secretary; Abortion; Civil rights; Consumer protection; Diplomatic and consular service, American -- Luxembourg; Disarmament; Discrimination; Energy policy; Environmental policy; Housing policy; Inflation (Finance).; Iran Hostage Crisis, 1979-1981.; Medical policy; Nuclear energy; Public welfare; Social security; Urban policy; Iran -- Foreign relations -- United States; Luxembourg -- Foreign relations -- United States; United States -- Emigration and immigration; United States -- Foreign relations -- Iran; United States -- Foreign relations -- Luxembourg; United States -- Politics and government -- 1977-1981.; Washington (D.C.) -- Politics and government; Cabinet officers; Diplomats; Educators; Lawyers